Overexpression of the Endosomal Anion/Proton Exchanger ClC-5 Increases Cell Susceptibility toward Clostridium difficile Toxins TcdA and TcdB - Ruhe, Frederike; Olling, Alexandra; Abromeit, Rasmus; Rataj, Dennis; Grieschat, Matthias; Zeug, Andre; Gerhard, Ralf; Alekov, Alexi (Frontiers in Cellular and Infection Microbiology, 2017)
Virulent C. difficile toxins TcdA and TcdB invade host intestinal epithelia by endocytosis and use the acidic environment of intracellular vesicles for further processing and activation. We investigated the role of ClC-5, a chloride/proton exchanger expressed in the endosomes of gastrointestinal epithelial cells, in the activation and processing of C. difficile toxins. Enhanced intoxication by TcdA and TcdB was observed in cells expressing ClC-5 but not ClC-4, another chloride/proton exchanger with similar function but different localization. In accordance with the established physiological function of ClC-5, its expression lowered the endosomal pH in HEK293T cells by ~0.6 units and enhanced ~five-fold the internalization of TcdA. In colon HT29 cells, 34% of internalized TcdA localized to ClC-5-containing vesicles defined by colocalization with Rab5, Rab4a, and Rab7 as early and early-to-late of endosomes but not as Rab11-containing recycling endosomes. Impairing the cellular uptake of TcdA by deleting the toxin CROPs domain did not abolish the effects of ClC-5. In addition, the transport-incompetent mutant ClC-5 E268Q similarly enhanced both endosomal acidification and intoxication by TcdA but facilitated the internalization of the toxin to a lower extent. These data suggest that ClC-5 enhances the cytotoxic action of C. difficile toxins by accelerating the acidification and maturation of vesicles of the early and early-to-late endosomal system. The dispensable role of electrogenic ion transport suggests that the voltage-dependent nonlinear capacitances of mammalian CLC transporters serve important physiological functions. Our data shed light on the intersection between the endocytotic cascade of host epithelial cells and the internalization pathway of the large virulence C. difficile toxins. Identifying ClC-5 as a potential specific host ion transporter hijacked by toxins produced by pathogenic bacteria widens the horizon of possibilities for novel therapies of life-threatening gastrointestinal infections.